Factors Affecting Customers Brand Switching Behavior in Mobile Telecommunication Industry: A Study of Pabna District in Bangladesh - Masud-Ul-Hasan, Md. (Asian Business Review, 2016)
The mobile telecommunication market in Bangladesh has already been saturated. In this matured market every company wants to protect their customer from being switched to their competitors. On the other hand, every company tries to attract the competitor’s customer. In this situation it is very important to understand every detail of the customers switching behavior. This study was intended to identify the factors affecting brand switching behavior as well as the factors which create the switching barrier.
Keywords: Mobile telecommunication industry; Customer loyalty; switching behavior; switching barrier